Analisis Bentuk Musik atas Kesenian Laras Madya dan Resistensinya dalam Budaya Jawa - Sagaf Faozata Adzkia (PROMUSIKA, 2016)
The Laras madya is a development form of Santiswaran music from the time of Pakubuwono X (1893-1930)  in Kasunanan Surakarta. This is a Javanese-Islamic cultures blend of music that its song lyric is based on the Serat Wulangreh text written by Pakubuwono IV. The Laras Madya instrumentation is generally utilized traditional percussions such as the kendang, the terbang dhana, the terbang gong, and the two-pitches saron, to accompany the Bowo (solo singer), and the Gerong (accompanist singer).  This study discusses the uniqueness of Larasa Madya’s musical form and its resistance from the domination of mass culture. Therefore, this research is aimed to describe and analyze the Laras madya’s musical form, and the resistance. This study applies interdisciplinary approaches to musicology, cultural studies, and socio-anthropology, through qualitative methods. This study result indicates that the Laras madya is a form of Javanese ensemble which characterized by rhythm repetition, the use of the Slendro pentatonic melody, constant expression, and moderate-andante tempo.  To resist from the hegemony of mass culture, the Laras Madya owns some efforts to form such public opinion/ campaign through cultural festival media, as its open resistance characteristic, and also to raise rumors on the negative image of mass culture as a class domination that is conducted bt individuals, as the trait of closed resistance.